(3GdhbGFY GdGbJUGOjI (B:s (3GdYhdeI GdGbJUGOjI(B-(3GdJfejI GdeSJOGeI (B/s - (3NHGHI, YHO Gddgs; (3HhbQI, QGHM s ((3GdGScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2009)
(3GdhbGFY GdGbJUGOjI ef GdJGQjN GdbOje Edi HOGjI GdbQf GdYTQjf,GdCMOGK GdGbJUGOjI aj GdJGQjN GdbOje,GdhbGFY GdGbJUGOjI aj GdHdGO GdGSdGejI bHd GdGSJYeGQ GdQCSeGdj,GdGbJUGO GdEbWGYj aj ChQhHG,GdfgVI GdGbJUGOjI hHfGA GdfXGe GdQCSeGdj,GdhbGFY GdGbJUGOjI GdeYGUQI,GdhbGFY GdGbJUGOjI aj EaQjbjG bHd GdGSJYeGQ GdQCSeGdj,GdYhdeI,GdYhdeI GdGbJUGOjI,BKGQ GdYhdeI GdGbJUGOjI,GdJfejI GdeSJOGeIs
(3GdeQGLY U(B.385 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdEbJUGOs; (3GdJGQjN(B- (3GdEbJUGOs; (3GdJfejI GdEbJUGOjIs; (3GdJfejI GdeSJOGeIs